The photo-oxidation of benzyl alcohol over TiO2 and Pt TiO2 and the effect of reaction conditions - Mlangeni, Nomathamsanqa (Department of Chemical Engineering, 2024)
The fine chemical benzaldehyde is commonly produced by the oxidation of benzyl alcohol (B-Alc) using stoichiometric amounts of hazardous oxidants such as chromates. The selective, photocatalytic oxidation of benzyl alcohol offers a promising, more environmentally friendly method of producing benzaldehyde. In this work, the hypothesis that platinum enhances the photocatalytic activity of titania in the photocatalytic oxidation of benzyl alcohol was tested. The titania tested was commercially sourced and the platinum was anchored on titania using a wet impregnation method, with H2PtCl6.6H2O as the precursor salt. The synthesized platinum catalysts were characterized using PXRD, TEM, BET, ICP – OES. The spent catalysts were characterized using TEM, Raman, TGA and ATR-FTIR. The catalysts were tested for their activity and selectivity in the aerobic oxidation of benzyl alcohol in a Lelesil photochemical reactor. In the photocatalytic testing, the effect of reaction conditions in the photooxidation of benzyl alcohol over titanium dioxide (Degussa P25) in toluene as a solvent, were investigated. The reaction is photoinduced, as no reaction was observed under dark conditions, but a conversion of benzyl alcohol of ca. 20% was recorded under ultraviolet and of ca. 9% under visible irradiation after a reaction time of eight hours. The photo-catalytic oxidation of benzyl alcohol is selective to benzaldehyde (≥99%). The rate of reaction increases with increasing stirring speed, indicating the existence of a mass transfer regime. However, above 250rpm, reaction rate does not change with increasing agitation speed, indicating the absence of mass transfer limitations at this stirring rate. A stagnation in the rate of reaction at high catalyst amounts was observed, which is dependent on the efficient utilisation of photons with respect to catalyst mass. The conversion initially increases with increasing reaction time, but the conversion-time curve starts flattening out after some time, suggesting catalyst deactivation. Carbon deposition as the origin of catalyst deactivation was confirmed using thermal gravimetric analysis of the spent catalyst. The rate of reaction over Pt – P25 was 0.08 mmol/g/hr and that over P25 was only 0.05 mmol/g/hr. This shows the enhancement in the rate of the photocatalytic oxidation over Pt – P25 compared to pure P25.